Implementation Of The Wakalah Wal Murabahah Agreement In PT. Future Package Financing - Ahmad Day Robi; Yenni Samri Juliati Nasution; Nursantri Yanti (PT. Islamic Research Publisher, 2023)
In general, Future Package Financing (PMD) is a product from BTPN Syariah which is given to underprivileged women in rural areas who can be used for business development. PMD uses a wakalah wal murabahah contract. This research aims to find out about the implementation of the wakalah wal murabahah agreement in PT Future Package (PMD) financing products. BTPN Syariah KCP Panyabungan. The research approach used in this research is descriptive qualitative with data collection methods, namely using observation, interviews and documentation studies. The results of the research concluded that the implementation of the wakalah wal murabahah agreement in PT Future Package (PMD) financing. BTPN Syariah KCP Panyabungan uses DSN-MUI Fatwa No. 4 of 2000 concerning Murabahah, as a legal basis, there is a discrepancy, because the murabahah contract is executed before the wakalah contract. And the object of the contract is only in the form of money, the bank only offers a limit for money loans, not buying and selling (murabahah), the profit sharing margin is 30% which is taken not from profits from buying and selling goods (murabahah) so it is the same as borrowing money at conventional banks.